2013
DOI: 10.1103/physrevb.87.224427
|View full text |Cite
|
Sign up to set email alerts
|

Transition from one-dimensional antiferromagnetism to three-dimensional antiferromagnetic order in single-crystalline CuSb2O6

Abstract: Measurements of magnetic susceptibility, heat capacity and thermal expansion are reported for single crystalline CuSb2O6 in the temperature range 5 < T < 350 K. The magnetic susceptibility exhibits a broad peak centered near 60 K that is typical of one-dimensional antiferromagnetic compounds. Long-range antiferromagnetic order at TN = 8.7 K is accompanied by an energy gap (∆ = 17.48(6) K). This transition represents a crossover from one-to three-dimensional antiferromagnetic behavior. Both heat capacity and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 33 publications
(60 reference statements)
6
35
1
Order By: Relevance
“…For one sample of CuSb 2 O 6 it was recently reported that in the AFM ordered state easy axis and spin flop was observed for both a and b directions [12]. Indeed, the reported decrease of susceptibility along both a and b axis in that sample was comparable in magnitude corroborating this claim.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…For one sample of CuSb 2 O 6 it was recently reported that in the AFM ordered state easy axis and spin flop was observed for both a and b directions [12]. Indeed, the reported decrease of susceptibility along both a and b axis in that sample was comparable in magnitude corroborating this claim.…”
Section: Discussionsupporting
confidence: 76%
“…The orientation of (7) • , in good agreement with previously published data [1]. Presence of multiple twins, reported by other authors [2][3][4][12][13][14], was also observed in our data.…”
Section: A X-ray Diffractionsupporting
confidence: 83%
See 3 more Smart Citations